Threading Jewish Identity: The Sara Stern in Sonia Delaunay. Issue 1 (2nd January 2016) - Levin, Gail
Abstract : This essay aims to understand and contextualize the Jewish identity of the artist Sonia Delaunay, who, in 1885, was born Sara Stern to a poor family in Gradizhsk, southeast of Kiev in Ukraine, well within the Pale of Settlement, where the Russian Empire permitted Jews to live. This essay argues that her early surroundings in Ukraine affected the formation of both her aesthetic and Jewish identity. From the age of seven, she grew up in St. Petersburg, in the home of her rich maternal uncle. Rather than looking for intentional Jewish content or motifs in her art, this essay attempts to tease out the ways that her life engaged Jewish culture—from the folk culture of her early childhood in Ukraine and her sophisticated adolescence in St. Petersburg, to art school in Karlsruhe, Germany, and the worlds of avant-garde art and haute couture in Paris. Any public acknowledgement of her Jewish identity was limited by her awareness and experience of anti-Semitism in Ukraine, Russia, Germany, and France. The bold self-image she projected as a modernist and as an outsider, coupled with her eager embrace of the new, reads as her individual response to traditional society's rejection of the Jews.